Latest Developments in Modeling and Characterization of Joining Metal Based Hybrid Materials. Issue 9 (23rd May 2018) - Khoddam, Shahin; Tian, Liang; Sapanathan, Thaneshan; Hodgson, Peter D.; Zarei‐Hanzaki, Abbas
Abstract : Advanced materials consist of several materials systems that exhibit complementary properties for multi‐purpose applications. Joining of dissimilar materials is a critical and challenging advanced manufacturing technique to develop novel hybrid materials with properties fully transferred. The "bonding strength" of a joint is crucial for its integrity and performance. The bonding strength is affected by a range of parameters that can be better understood, controlled, and optimized via both experimental and analytical approaches. In this paper, the authors review the theoretical and experimental studies of the interface inside several metal based composites. The scope includes interface bonding's critical parameters, characterization techniques of joining processes, potential applications, and their future perspectives. The review is significant to develop advanced manufacturing techniques for heterogeneous materials and to design innovative heterogeneous systems for various medical, electrical, electronics, industrial, and other daily life applications that involve the broad range of "joining" processes. Abstract : Design of innovative hybrid materials for various applications involves a broad range of "joining" processes. This article presents a review on theoretical and experimental aspects of the joints, their interface bonding's critical parameters, characterization techniques, potential applications, and their future perspectives.